2021
DOI: 10.1063/5.0061086
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical dynamics of epidemic propagation and awareness diffusion in multiplex networks

Abstract: To better explore asymmetrical interaction between epidemic spreading and awareness diffusion in multiplex networks, we distinguish susceptibility and infectivity between aware and unaware individuals, relax the degree of immunization, and take into account three types of generation mechanisms of individual awareness. We use the probability trees to depict the transitions between distinct states for nodes and then write the evolution equation of each state by means of the microscopic Markovian chain approach (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In practice, the different information perception abilities of individuals and the different conscious responses of different individuals who are informed of information also have an impact on disease transmission. [22][23][24][25][26] Sun et al [22] studied the asymmetric interaction between disease transmission and consciousness diffusion in multiple networks, distinguishing susceptibility and infectiousness between conscious and unconscious individuals, and the results showed that the introduction of self-awareness in infected individuals increased. Chang et al [25] investigated the effect of the heterogeneity of information layers on disease transmission thresholds, and showed that weak heterogeneity of information layers was more effective in inhibiting disease transmission than strong heterogeneity when the rate of consciousness transmission was within a certain range.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the different information perception abilities of individuals and the different conscious responses of different individuals who are informed of information also have an impact on disease transmission. [22][23][24][25][26] Sun et al [22] studied the asymmetric interaction between disease transmission and consciousness diffusion in multiple networks, distinguishing susceptibility and infectiousness between conscious and unconscious individuals, and the results showed that the introduction of self-awareness in infected individuals increased. Chang et al [25] investigated the effect of the heterogeneity of information layers on disease transmission thresholds, and showed that weak heterogeneity of information layers was more effective in inhibiting disease transmission than strong heterogeneity when the rate of consciousness transmission was within a certain range.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [25] further explored the influence of local awareness in an epidemic transmission model in multiplex networks, and discovered the ratio of local awareness possessed a two-stage cascade of effects on the epidemic threshold and the final epidemic size. Sun et al [26] introduced three types of generation mechanisms of individual awareness in multiplex networks, and indicated that increasing self-awareness among infected individuals not only reduces the prevalence of the epidemic but also increases the epidemic threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Peng et al [47] proposed a behavior spreading model to describe the heterogeneity of individuals in adopting the behavior, in which the adoption threshold follows the Gaussian distribution. Sun et al [48] distinguished susceptibility and infectivity between aware and unaware individuals, relaxed the degree of immunization, and took into account three types of generation mechanisms of individual awareness. Tian et al [49] considered edge weight distribution and adoption heterogeneity on the networks separately, where the adoption thresholds of nodes obey truncated Gaussian distribution.…”
Section: Introductionmentioning
confidence: 99%